The Correlation Between Core Competency-Oriented Curriculum Implementation and the Development of Students' Higher-Order Thinking: A Case Study of Inquiry-Based Teaching in High School Science - Wang, Han; Wang , Quanwang (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This study aimed to 1) explore the relationship between core competency-oriented curricula and the development of higher-order thinking skills in high school science education, 2) analyze the impact of inquiry-based teaching on students' analytical, evaluative, and creative thinking abilities, and 3) examine the challenges and opportunities associated with the implementation of core competency-oriented and inquiry-based teaching strategies in high school science classrooms. The sample consisted of 90 high school science students from three different schools in a city, randomly divided into experimental and control groups. The experimental group received core competency-oriented curriculum combined with inquiry-based teaching, while the control group followed traditional teaching methods. Data were collected through pre- and post-intervention surveys, focusing on students’ higher-order thinking abilities, including analysis, evaluation, and creativity. Additionally, semi-structured interviews were conducted with 6 teachers involved in the teaching process together insights into their experiences and challenges. The research results were found as follows; 1) The experimental group showed significant improvements in their higher-order thinking skills compared to the control group, with gains in analysis, evaluation, and creativity (p<0.05), 2) Teachers observed increased student engagement, critical thinking, and problem-solving abilities in the experimental group, and 3) The main challenges included time management and balancing inquiry activities with content coverage, but opportunities for improvement were found in teacher training and the use of educational technology. The findings provide valuable insights into the effectiveness of integrating core competency-oriented curricula with inquiry-based teaching to enhance students' cognitive skills and suggest practical strategies for overcoming challenges in high school science education.